AB0304 The delay in the management of rheumatoid arthritis by a rheumatologist is associated with an alteration of the function of the foot. (12th June 2018) - Afilal, S.; rkain, H.; fellous, S.; tahiri, L.; alami, N.; guieu, R.; jammes, Y.; allali, F.; Hajjaj-Hassouni, N.
Abstract : Background: Impairment of foot function is known in rheumatoid arthritis. Objectives: Evaluate the functional status of the foot in patients with RA and look for factors associated with impaired foot function. Methods: This is a cross-sectional study that consecutively included 14 patients (100% female, mean age 55.3 years) with RA (median duration of evolution of 13.5 years, mean specialised care of 2.1 years). The functional status of RA was assessed by the HAQ (Health Assessment Questionnaire). RA activity was evaluated by DAS28 and DAS44. The FFI score (Foot Function Index) was used to determine the functional status of the foot. A correlation analysis was made between the FFI score and DAS28, DAS44 and HAQ as well as with the duration of progression of the RA and the delay of specialised management. Results: The median score of the HAQ (Health Assessment Questionnaire) was 1.6. The median score for the Foot Function Index (FFI) was 53.6. The medians of DAS 28 and DAS 44 were 5.3 and 3.8. The median of the different FFI score items was: Pain Sub-scale: How severe is your foot pain ? Q1: Foot pain at its worst ? 7 (6; 9, 25), Q2: Foot pain in morning ? 5, 5 (2; 7), Q3: Pain walking barefoot ? 4 (1, 75; 8, 15), Q4: Pain standing barefoot ? 5 (3, 25; 8, 25), Q5: Pain walking with shoes ? 4 (1, 75; 5, 75), Q6: Pain standing with shoes ? 4, 5 (3; 5, 5), Q7: Pain walking with orthotics ? 3 (3; 3), Q8: Pain standing with orthotics ? 3 (3; 3), Q9: Foot pain at end of day ? 5 (2, 75; 7) Disability sub-scale: How much difficulty did you have ? Q10: Difficulty walking in house ? 2 (0; 3, 25), Q11: Difficulty walking outside ? 5, 5 (3; 8), Q12: Difficulty walking 4 blocks ? 5 (4; 9), Q13: Difficulty climbing stairs ? 6, 5 (4; 8, 25), Q14: Difficulty descending stairs ? 6 (3, 5; 8, 25), Q15: Difficulty standing tip toe ? 8, 5 (5, 25; 10), Q16: Difficulty getting up from chair ? 5 (1, 5; 8), Q17: Difficulty climbing curbs ? 4, 5 (2; 7, 25), Q18: Difficulty walking fast ? 8, 5 (4, 75; 10) Activity Limitation sub-scale: How much of the time do you ? Q19: Stay inside all day because of feet ? 7 (2; 8, 25), Q20: Stay in bed all day because of feet ? 5 (2; 3, 25), Q21: Limit activities because of feet ? 5, 5 (1; 8), Q22: Use assistive device (cane, walker, crutches, etc) indoors ? 0 (0; 3, 25), Q23: Use assistiw device (cane, walker, crutches, etc) outdoors ? 0 (0; 0, 75). No correlation was found between the FFI and the HAQ. DAS 28 and DAS44 did not correlate with the FFI either. Alteration of foot function as indicated by a high FFI score was associated with a delay in specialist management by a rheumatologist (r=0.535, p=0.04). Conclusions: This study provides insight into the impact of RA on foot function. The HAQ, DAS28 and DAS44 would not reflect the functional deterioration of the foot in RA. In addition, an alteration of foot function would be associated with a delay in specialist management by a Rheumatologist. A large-scale study is underway to validate and complete these preliminary results. Disclosure of Interest: None declared